High-Efficiency WOLEDs with High Color-Rendering Index based on a Chromaticity-Adjustable Yellow Thermally Activated Delayed Fluorescence Emitter - Li, Xiang-Long (Advanced materials (Deerfield Beach, Fla.), 2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.